The impact of exchange rate regimes on economic growth: Empirical study of a set of developing countries during the period 1974–2006 - Ashour, Majidah; Yong, Chen Chen (Taylor & Francis, 2018)
An increment in the quantity of services/goods manufactured per-head of the population over time denotes economic growth of a country. Exchange Rate Intermediate Regimes are unable to continue under conditions of capital movement. To examine the relationship between exchange rate regimes and economic growth. This study has kept its focus on the economic growth of a set of developing countries during the years (1974–2006). Fixed effects and pooled regression for 16 developing countries have been incorporated as the methodologies techniques for data. Analysis of data was performed through SPSS. A relationship between exchange rate regimes and economic growth has been identified through statistical approaches. The results indicated that as compared to flexible exchange regime, growth rate was higher by 1.2% when fixed exchange regime was adopted; and a growth rate of 0.64% was achieved under the intermediate regime when compared with the flexible regime. A positive impact has been identified in exchange rate regimes upon economic growth of the developing countries. Countries following the flexible exchange rates are facing scarcity for the existence of advanced financial systems, which deprives them of enjoying the benefits of flexible regime.